AB0725 Severe dysphagia "poor prognostic marker" in idiopathic inflammatory myopathies. (12th June 2018) - Costi, A.C.; Garcìa, L.; Pena, C.; Testi, A.; Sansinanea, P.; Aguila, R.; Pera, M.; Velloso, S.; Savy, F.; Garcìa, M.
Abstract : Background: In Idiopathic Inflammatory Myopathies (MII), 18%–20% of patients have dysphagia. Objectives: To evaluate the frequency of dysphagia in patients with MII, association with other manifestations of the disease, treatment and evolution. To evaluate clinical characteristics and evolution of severe dysphagia. To compare clinical characteristics and evolution of mild-moderate versus severe dysphagia. Methods: Retrospective, observational study. Patients with a diagnosis of MII were included according to modified classification criteria of Bohan and Peter. Demographic, clinical and complementary studies were recorded. Serious dysphagia was considered: contraindication of oral feeding. Descriptive statistics were performed. Chi2 test, Student's test or Mann Whitney as appropriate. Results: We included 91 of 106 patients evaluated from 1992 to 2017: 76% female, mean age at diagnosis 48±14 years. 53% presented dysphagia: mild/moderate 62.5% (30/48 pts), severe 37.5% (18/48). Idiopathic dermatomyositis was the most frequent MII in these patients (71%). In patients with dysphagia, proximal muscle weakness was 90%, weakness of neck muscles 45%, weakness of respiratory muscles 27%. A significant association was found between dysphagia and weakness of respiratory muscles, weak neck muscles, glucocorticoid pulses, gammaglobulin, grave infections and death. (Data not shown in the summary). In patients with severe dysphagia, we observed a significant association with the requirement for mechanical ventilation, hospitalisation in an intensive care unit, serious infections and death (table 1). When comparing mild-moderate dysphagia vs severe dysphagia, a statistically significant association was found with neck muscles weakness, respiratory muscle weakness, glucocorticoid pulses, gamma globulin use, requirement for mechanical ventilation, hospitalisation in an intensive care unit, severe infections and mortality (table 2). Conclusions: Fifty-three percent of patients with MII had dysphagia at some point during their evolution. Severe dysphagia was associated with parameters of disease severity, poor prognosis and increased mortality. Disclosure of Interest: None declared